TANTANGAN BIMBINGAN DAN KONSELING DI ERA GLOBALISASI DAN DIGITALISASI - Reizki Maharani; Karneli, Yeni; Ifdil; Netrawati (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The era of globalization and digitalization has brought significant changes to guidance and counseling services, both in terms of challenges and opportunities. This study aims to analyze various challenges faced by guidance and counseling professionals amid technological transformation and socio-cultural changes. The method used is a descriptive literature review of recent national and international articles. The analysis shows that the main challenges include adaptation to new technologies, the digital divide, ethical and privacy issues, as well as the need for the development of multicultural competence and digital literacy for counselors. On the other hand, digitalization also opens up opportunities to expand service access, increase efficiency, and develop innovative interventions that are more responsive to client needs. This study recommends the need for continuous training, strengthening data protection policies, and cross-disciplinary collaboration to improve the quality of guidance and counseling services in the era of globalization and digitalization.